A new method for online measurement of the concentration of working fluids in absorption refrigeration systems. (June 2017) - Jiang, Jingkai; He, Guogeng; Liu, Yilin; Li, Keqiao; Cai, Dehua
Highlights: A new method for concentration measurement of absorption working pair is presented. Electrical conductivity with different temperatures and concentrations is obtained. A new correlation for solution concentration calculation is provided. Abstract: This paper proposes a new method for online measurement of the concentration of working fluids in absorption refrigeration systems: electrical conductivity is measured to determine the concentration of the solution. Compared with the common density-concentration method, electrical conductivity-concentration method has the same accuracy but helps to save cost when applied in absorption systems with ammonia–salt solutions. This novel method is also suitable for systems with traditional working fluids like water–lithium bromide solution. Electrical conductivities of ammonia–lithium nitrate, ammonia–sodium thiocyanate and water–lithium bromide solutions were measured between (293.15 and 333.15) K, using an Industrial Conductivity Meter. The ammonia mass fraction varied from 0.35 to 0.48 for ammonia–lithium nitrate solution and from 0.35 to 0.50 for ammonia–sodium thiocyanate solution. For water–lithium bromide solution, the mass fraction of lithium bromide was within the range of 40%–60%. The experimental data were correlated as a function of temperature and composition using the extended Casteel–Amis equation. In addition, correlations of refrigerant mass concentration as a function of electrical conductivity and temperature of the solution are proposed.